Humor in banking TikTok communication: Motives for media use and brand image building - Zahra, Xhavira Clara; Ali, Dini Salmiyah Fithrah (Universitas Padjadjaran, 2026)
Background: The increasing use of TikTok as a short-video platform has prompted banking institutions to adopt humorous content as part of their digital communication strategies. However, empirical studies examining the role of audience motives for media use and affective mechanisms in shaping banking brand image through humorous content remain limited. Purpose: This study aims to examine the influence of Motives for TikTok use on audience perception of humorous banking content and banking brand image, and the mediating role of such content. Methods: This study adopts a quantitative explanatory approach using a survey method. Data were collected from 403 Indonesian TikTok users who had been exposed to humorous content from Bank A’s official TikTok account and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results: The results show that motives for media use significantly affect perceptions of humorous content and directly influence banking brand image. Such content also positively affects brand image and partially mediates this relationship. Conclusion: The study results suggest that the banking brand image on TikTok is shaped by the audience’s media use patterns and the affective experiences generated through humor-based content. Implications: The study contributes to the application of the Uses and Gratifications theory in the context of digital banking communication and recommends that banking organizations create humorous TikTok content aligned with audience motivations, while maintaining professionalism, credibility, and contextual relevance.